Engineering geology evaluation for predicting the collapse susceptibility of Sidoarjo hot mud earth levees: A hazard assessment - Doni Prakasa Eka Putra; Juwarso Juwarso; Dwikorita Karnawati (Journal of Applied Geology, 2015)
Since May 29, 2006, a sea of hot mud has been gushing from the ground in Sidoarjo, East Java, 35 kilometres south of Indonesia’s second largest city, Surabaya. Due to this disaster, approximately thousand of peoples have been forced from their homes because 600 ha of land and villages were submerged, farmland was ruined, businesses and schools closed as the mud inundated the surrounding area. The authorities response was to build containment ‘basins’ or ‘ponds’ by enclosing areas of land within earth dams, or levees. During the heavy rain on the rainy season, the earth dams and ringdykes have overflown and broken regularly, causing the flooding of more land and damaging infrastructures. However, not only in the rainy season, the levees had also collapses during the dry season. Therefore, an engineering geology study was conducted in order to evaluate the geological factors which causes this phenomena. The parameters used for the evaluation are the heterogeniety of lithology under the dams, geological discontinuity which indicated by the occuring of surface cracks and bubbles, and subsidence phenomena which indicated by the vertical displacement. Overlying method was used to build homogeniety zone of engineering geology based on those parameters, and the resulted map was once again overlay with the location of dams collapses. Result of this evaluation shows that the earth dams collapses were highly correlated with the existing geological discontinuities and subsidences, respectively. Based on this study, the susceptible location of earth dams collapses can be predicted and allow engineers to prepare and plan better engineering solution for the high probable collapses points in order to protect land and infrastructures from the damaging hot mud overflown. Keywords: Hot mud disaster, geological factors, homogeniety zone, earth levee failure points, Sidoarjo-Indonesia